The Role of Islamic Education Teachers in Forming Religious Character of Students Through Extracurricular Pesantren Kilat Activities - Tatang Sholahuddin Ma’ruf; Ahmad Khoiri (Journal of Science and Education (JSE), 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in shaping students’ religious character through Pesantren Kilat (short-term Islamic boarding school programs) in two junior high schools with differing institutional approaches. Employing a descriptive qualitative method and data triangulation (observation, interviews, and documentation), the study reveals that SMPN 50 adopts a massive training model based on rotating modules, while SMP Triyasa employs a small-group mentoring approach. The findings indicate that SMPN 50 excels in the practice of religious rituals, whereas SMP Triyasa is stronger in spiritual internalization. Additionally, four key roles of PAI teachers were identified: spiritual architect, moral model, cultural translator, and ethical coach, all of which contribute significantly to the contextual internalization of religious values. Program evaluation results show an increase in religiosity by 23% at SMPN 50 and 18% at SMP Triyasa, though value retention after six months was higher at SMP Triyasa (85%) than at SMPN 50 (72%). These findings support the theories of deep learning and Resource-Based Pedagogy, which emphasize the importance of interaction quality and strategic adaptation to institutional capacity. The study also proposes a Triaxial Character Development model integrating spiritual, social, and cognitive dimensions as an effective framework for Islamic character education. Practical implications include the development of an adaptive Pesantren Kilat model based on students’ needs and a sustainable system for spiritual evaluation.